THE RELATIONSHIP OF ENERGY ADEQUACY LEVELS, NUTRITIONAL STATUS, PHYSICAL ACTIVITY AND MENSTRUAL CYCLE IN STUDENTS OF STATE HIGH SCHOOL 7 KENDARI - Fithria, Fithria; Parida, Parida; Anggraeni, Wa Ode Wulan (Preventif Journal, 2024)
ABSTRACT Menstrual cycle disorders can affect quality of life, activities and can result in reproductive health problems, for example decreased fertility, oligomenorrhea, infertility and anemia. Differences in menstrual cycles can be caused by several factors. The aim of this research is to determine the relationship between the level of energy adequacy, nutritional status, and physical activity on the menstrual cycle of female students at SMA Negeri 7 Kendari. This research uses an analytical observational research design with a cross sectional study. The research used a proportional random sampling technique with a sample size of 66 respondents. Data analysis used univariate and bivariate analysis using the chi-square test. The results of statistical analysis on the energy adequacy level variable obtained a value of (p=0.391), on the nutritional status variable a value was obtained (p=0.004), and on the physical activity variable a value was obtained (p=0.031). The results of the statistical analysis of the three variables obtained an energy adequacy value of p > 0.05 , which means there is no relationship between the level of energy adequacy and the menstrual cycle, while the nutritional status and physical activity variables are p